2019
DOI: 10.1111/str.12318
|View full text |Cite
|
Sign up to set email alerts
|

A reliable in vitro approach to assess the stability of acetabular implants using digital image correlation

Abstract: The main cause of failure of the hip acetabular component is aseptic loosening. Preclinical test methods currently used to assess the stability of hip acetabular implants rely on crude simplifications. Normally, either one component of motion or bone strains are measured. We developed a test method to measure implant 3D translations and rotations and bone strains using digital image correlation. Hemipelvises were aligned and potted to allow consistent testing. A force was applied in the direction of the load p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…This was justified by previous investigations. In particular, our study relied on an extensively validated testing method based on Digital Image Correlation, which provided very small measurement errors [ 22 ]. To overcome the inter-specimen variability, paired hemipelvises were used, allowing more powerful statistical analysis based on paired data.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This was justified by previous investigations. In particular, our study relied on an extensively validated testing method based on Digital Image Correlation, which provided very small measurement errors [ 22 ]. To overcome the inter-specimen variability, paired hemipelvises were used, allowing more powerful statistical analysis based on paired data.…”
Section: Discussionmentioning
confidence: 99%
“…The loading configuration was limited to a single direction, reducing the complexity of forces and moments acting in the acetabulum. Such an approach, already adopted by most authors, has been proved to induce cup motions comparable with ones clinically observed while granting a good robustness and reliability to the results (i.e., minimizing the sources of experimental error [ 22 ]). Moreover, as paired tests were performed, the effect of the loading configuration on the acetabular stability was reduced in comparison with the effect of the reconstruction material.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Motion increased with increasing load (Figure 4), which is in good accordance with previous primary stability studies under dynamic load. 26,35 in human donor specimens. Under uniaxial dynamic loading in the same direction as applied in the present study, they found that inducible displacements and migrations were slightly higher (but without statistically significant difference) for tetrapods + coll than for bone chips throughout all applied load packages from 0.5*BW to 3.0*BW, which corresponded to median values of approximately 387 and 2325 N based on the donors' weight.…”
Section: Discussionmentioning
confidence: 99%